2015
DOI: 10.1210/jc.2014-2523
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone to Dihydrotestosterone Ratio as a New Biomarker for an Adverse Metabolic Phenotype in the Polycystic Ovary Syndrome

Abstract: Our data provide evidence for a strong link between a high TT/DHT ratio and an adverse metabolic phenotype in PCOS patients. This correlation was only found in PCOS patients, suggesting the TT/DHT ratio to be a new biomarker for an adverse metabolic phenotype in PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 27 publications
7
55
0
3
Order By: Relevance
“…In fact, increasing evidence supports that androgen excess represents a constitutive biomarker of PCOS. As expected, an androgen profile rather than testosterone alone should be used, as documented by several recent studies (12,13,14,15,16,18). A fundamental prerequisite is represented by the fact that if different androgens are needed to fully define hyperandrogenemia in these women, it could be that different mechanisms may be involved in regulating the enzyme activity involved in the androgen production rate or in their metabolic clearance rate (18).…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, increasing evidence supports that androgen excess represents a constitutive biomarker of PCOS. As expected, an androgen profile rather than testosterone alone should be used, as documented by several recent studies (12,13,14,15,16,18). A fundamental prerequisite is represented by the fact that if different androgens are needed to fully define hyperandrogenemia in these women, it could be that different mechanisms may be involved in regulating the enzyme activity involved in the androgen production rate or in their metabolic clearance rate (18).…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 96%
“…Several recent studies have shown that extremely accurate and sensitive technologies in the detection and analysis of steroids, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) (8), have significantly improved the definition of the androgenemic blood pattern in women with PCOS (11,12,13,14,15,16,17,18). These studies have clearly shown that a steroid profile, including not only testosterone blood levels but also androstenedione and the free androgen index (FAI), may optimize the diagnosis of hyperandrogemia in women with PCOS, therefore improving our understanding on the heterogeneity of its phenotypes.…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%
“…Therefore, there is the need to identify predictors that would help to identify PCOS patients with the highest metabolic risk. Münzker et al proposed total testosterone/dihydrotestosterone ratio (TT/DHT) as an indicator of a worse metabolic prognosis in PCOS [4]. Metabolic disturbances observed in patients with PCOS result from the unfavorable influence of androgens on glucose and lipid metabolism as well as on insulin action.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium supplementation may result in decreased serum DHEA levels and hirsutism through improved markers of insulin metabolism [13] and decreased oxidative stress [12]. Previous studies have demonstrated that a positive association between hyperandrogenism, hyperinsulinemia, and insulin resistance in females with elevated androgen levels due to PCOS [45,46]. In addition, oxidative stress is directly correlated with both insulin resistance and hyperandrogenism, which in turn contribute to endocrine and biochemical alterations in women with functional ovarian hyperandrogenism (FOH) [47].…”
mentioning
confidence: 99%